2009
DOI: 10.1007/s10334-009-0167-1
|View full text |Cite
|
Sign up to set email alerts
|

Design of internal MRI coils using ultimate intrinsic SNR

Abstract: An internal coil design method that takes advantage of the UISNR and optimum coil sensitivity calculations was presented. This method can also be used to design better internal MRI coils for different applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…For a similar stripline element, Eryaman et al (13) have shown that the optimal intrinsic SNR can be obtained with a 4 cm length element. In our case, the stripline length is set to 6 cm to cover approximately the same area as the loop coil, while avoiding overlap between both elements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a similar stripline element, Eryaman et al (13) have shown that the optimal intrinsic SNR can be obtained with a 4 cm length element. In our case, the stripline length is set to 6 cm to cover approximately the same area as the loop coil, while avoiding overlap between both elements.…”
Section: Discussionmentioning
confidence: 99%
“…A 6‐cm‐long stripline coil was fabricated using 3‐mm‐diameter copper litz wire as the active conductor, similar to the design presented by Eryaman et al (13). Litz wire obtained from the shield of a coaxial cable was flattened and used as the electric ground plane of the stripline element.…”
Section: Methodsmentioning
confidence: 99%
“…At large radii, sensitivity tends to s/2πr 2 , where r 2 = x 2 + y 2 , and falls off with radial distance as 1/r 2 [9]. This variation can be corrected by multiplying the signal intensity of axial images by a correctly-centred function C(r 2 ) where r 2 = (x − x C ) 2 + (y − y C ) 2 and (x C , y C ) is the location of the coil axis (see e.g., [3]). However, there are peaks in sensitivity near the conductors that cannot easily be corrected.…”
Section: D Modelmentioning
confidence: 99%
“…Consequently, increased SNR can be obtained using coils with restricted fields of view (FOV), provided these match the target tissue [3], Many small internal coils have been developed for imaging lumens such as arteries, ducts and the gastrointestinal (GI) tract. For compatibility with clinical procedures these are normally based on endoscopes [4][5][6] or catheters [7][8][9][10], and devices for tracking have also been developed [11].…”
Section: Introductionmentioning
confidence: 99%
“…NTERNAL magnetic resonance imaging (MRI) using small coils has been demonstrated [1][2][3], but clinical acceptance is relatively slow. There are difficulties associated with delivery into the patient, MR compatibility of endoscopic tools and the non-uniform sensitivity of the coils.…”
Section: Introductionmentioning
confidence: 99%